Election Oversight Strategy by the Maros Regency Election Supervisory Body (Bawaslu) in Addressing Election Crimes - Muhajir, Ahmad; Husen, La Ode; Ahmad, Kamri (Fakultas Hukum, Universitas Muslim Indonesia, 2025)
This study analyzes election oversight strategies implemented by the Election Supervisory Body (Bawaslu) of Maros Regency in addressing election crimes following Constitutional Court Decision No. 135/PUU-XXII/2024, which promotes the integration of regional legislative elections with regional head elections. This redesign expands the scope of supervision, compresses electoral stages, and intensifies local political competition, thereby increasing the risks of vote-buying, mobilization of civil servants, and administrative manipulation. The study employs a non-doctrinal (empirical) legal research method with a socio-legal approach, using in-depth interviews with 30 informants (Bawaslu officials, sub-district supervisors/Panwascam, and polling station supervisors) and a literature review. The findings show that the oversight strategy is built through preventive measures based on multi-channel outreach and target segmentation, vulnerability mapping and risk-based patrols, continuous supervision throughout all electoral stages down to polling stations, and early enforcement through the Integrated Law Enforcement Center (Sentra Gakkumdu). While these strategies are relatively effective in reducing overt violations and strengthening tiered coordination, they remain constrained by limited human resources and facilities, a permissive culture toward vote-buying, local socio-political pressures, and weak initial evidence and delayed reporting that hinder case escalation to prosecution. These findings underscore the need to strengthen supervisory capacity, enhance public legal literacy, protect whistleblowers and witnesses, and optimize oversight technologies to ensure more effective and sustainable enforcement of election criminal law.